NILAI-NILAI KEADILAN SOSIAL DALAM PEMIKIRAN JOHN RAWLS DAN IMPLIKASINYA TERHADAP KETIMPANGAN SOSIAL - Reski Fadila; Intan Karlina (JURNAL AL-AQIDAH, 2025)
This article explores the values of social justice in John Rawls's political philosophy and its relevance to social inequality in developing countries, particularly Indonesia. Using a library research method, the study conceptually analyzes Rawls’s core principles of justice namely the principle of equal liberty and the difference principle as a moral foundation for designing a fair social structure, the research was conducted through a critical examination of various written sources, including books, scholarly journals, and academic articles related to Rawls’s theory of justice, social distribution, and the context of inequality in developing countries. The difference principle, which prioritizes benefits for the least advantaged, serves as a normative benchmark to assess social distribution and affirmative policies. This study also examines critical perspectives on Rawls's theory, including its limitations in non-Western contexts and the challenges associated with strengthening the role of the state as an agent of social justice. The findings indicate that despite its criticisms, Rawls’s framework remains relevant and can be used as a normative basis for formulating inclusive, democratic, and substantively just public policies in the context of developing nations.